Experimental Investigation of Electrohydrodynamic Effect on the Performance of Double Pipe Heat Exchanger - Kumbhar, S. V.; Jadhav, M. A.; Jadhav, A. R.; Bardiya, S. G. (Asian Review of Mechanical Engineering, 2018)
Heat exchanger is a device which transfers heat from one fluid to another fluid. For the improvement in performance of heat exchangers, several heat enhancement techniques have been successfully implemented. These techniques are active, passive and combined techniques. In the active techniques, some external forces, e.g. electric field, acoustic or surface vibration etc. require for heat transfer enhancement. Whereas in the passive techniques, fluid additives or special surface geometries require for heat transfer enhancement. Electrohydrodynamic (EHD) effect can be used to enhance heat transfer rate between two fluids. In this paper, the effect of electrical body force on the performance of double pipe heat exchanger is studied.